Implemensi Aksara Incung di Sungai Penuh - John Eka Powa (Jurnal Ilmiah Dikdaya, 2020)
In Kota Sungai Penuh, the existence of the incung script has actually been revitalized for its use by the Kerinci Government. Therefore, this study will analyze the strengths, weaknesses, opportunities and threats in the implementation of enchung in schools in Sungai Penuh City. This research is a qualitative descriptive study with primary data obtained by interviews and questionnaires from 20 respondents. Then the data are analyzed by using the Strength, Weakness, Opportunities and Threats (SWOT) methods. The result is From the results and discussion described above, this research concludes that, from the analysis of Strength, Weakness, Opportunities, and Threats (SWOT), there are strengths that are not too high compared to weaknesses, where the point of strength is only at the number 300. This means that the implementation of the Enchung script as a local content in Sungai Penuh City is still weak. To implementated of the Enchung script as local content in schools in Sungai Penuh City, it is recommended to provide a budget for the process of implementing the Enchung script local content program in Sungai Penuh City. Providing facilities and infrastructure, manuals and textbooks to support the teaching and learning process.